Entrepreneurıal Orıentatıon and Transformatıonal Leadershıp As Determınants of Employee Creatıvıty: The Medıatıng Role of Knowledge Sharıng - Yumhi Yumhi; Juliansyah Noor (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
Several studies have been investigated in recent years on entrepreneurial orientation in financial firms. However, these rarely link transformational leadership, entrepreneurial orientation, and employee creativity through knowledge sharing. Therefore, this research aims is to determine the impact of transformational leadership (TRL) and entrepreneurial orientation (EO) on employee creativity (EC) through knowledge sharing (KS). This study was gathered data from 280 employee-manager dyads at 20 financial firms in Indonesia. To evaluate mediator factors, we used a two-step method to SEM. The finding indicates that the TRL and EO influence KS and EC. Additionally, the results show the significant positive effect of TRL, EO, and EC through KS. Thus, the TRL, OE., and EC can be increased through KS by encouraging employees to share KS to contribute to EC. This article seeks to contribute to the current organizational behavior theory by elucidating the mediation role of KS. Additionally, some intriguing discoveries are presented that have not been investigated previously by other studies.